2020
DOI: 10.3390/s20030784
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Modelling for Unsupervised Analysis of Human Behaviour in Smart Cities

Abstract: The growth of urban areas in recent years has motivated a large amount of new sensor applications in smart cities. At the centre of many new applications stands the goal of gaining insights into human activity. Scalable monitoring of urban environments can facilitate better informed city planning, efficient security, regular transport and commerce. A large part of monitoring capabilities have already been deployed; however, most rely on expensive motion imagery and privacy invading video cameras. It is possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Environmental sensors (e.g., thermometers, humidity sensors, anemometers, and light sensors) have also been utilized to account for environmental effects in target applications [5,6]. Position information, which is typically collected by the global position system (GPS), enables understanding the behavior of GPS-equipped entities, such as human beings and vehicles [1]. Wireless smart sensors can significantly reduce the installation and maintenance costs of the monitoring system, in addition to allowing multi-sensor data to be collected from a dense network of sensors [7][8][9].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Environmental sensors (e.g., thermometers, humidity sensors, anemometers, and light sensors) have also been utilized to account for environmental effects in target applications [5,6]. Position information, which is typically collected by the global position system (GPS), enables understanding the behavior of GPS-equipped entities, such as human beings and vehicles [1]. Wireless smart sensors can significantly reduce the installation and maintenance costs of the monitoring system, in addition to allowing multi-sensor data to be collected from a dense network of sensors [7][8][9].…”
mentioning
confidence: 99%
“…The results indicated that the method helps to choose the computation methods used in simulating sludge bulking with minimized measurement costs. Qarout et al [1] used GPS data in probabilistic modeling to understand human behavior in urban areas. The proposed approach, the adaptive input hidden Markov model (AI-HMM), was shown to be capable of grouping different categories of human behavior trends and identifying time-specific anomalies.…”
mentioning
confidence: 99%